Overview Of The Level Of Knowledge Of Young Women About Breast Self-Examination As An Early Detection of Breast Cancer - Chika Salsa Ardhana; Zulfa Mahdiatur Rasyida (International Journal of Health Engineering and Technology, 2026)
Often due to late early detection despite the effectiveness of Breast Self-Examination (BSE) since adolescence. This study aims to describe the level of knowledge of female adolescents at Senior High School Batik 1 Surakarta about BSE. Using a quantitative descriptive design, the population was 682 female students, a sample of 87 female students via simple random sampling (Slovin formula). The BSE questionnaire instrument (18 Guttman items, valid r=0.389-0.745; reliable α=0.894), univariate frequency/percentage analysis via SPSS (classification: good 76-100%, sufficient 56-75%, low ≤55%). The results showed that 48.3% had sufficient knowledge, 42.5% had good knowledge, 9.2% had low knowledge; The majority were aged 14-17 years (97.7%), had not been exposed to information (77%), and had not practiced BSE (86.2%). The study concluded that the majority had sufficient knowledge, but needed intensive education to improve understanding and early detection behavior.